The Iranian Nuclear Crisis : A Memoir - Musavian, Hossein (Book collections on Project MUSE., 2012)
The first detailed Iranian account of the diplomatic struggle between Iran and the international community, The Iranian Nuclear Crisis: A Memoir opens in 2002, as news of Iran's clandestine uranium enrichment and plutonium production facilities emerge. Seyed Hossein Mousavian, previously the head of the Foreign Relations Committee of Iran'sSupreme National Security Council and spokesman for Tehran's nuclear negotiating team, brings the reader into Tehran's private deliberations as its leaders wrestle with internal and external adversaries. Mousavian provides readers with intim.